„Ostpolitikkens anden fase“. Socialdemokratiet og sikkerhedspolitikken 1975-88 - Mariager, Rasmus Mølgaard (Historisk Tidsskrift, 2015)
„The Second Phase of Ostpolitik“ The Danish Social Democratic Party’s National Security Policies, 1975-88 Between 1982 and 1988 the Danish parliamentary opposition, led by the Social Democratic Party, pressured the Conservative-Liberal minority governments to submit so-called Danish „footnotes“ to official NATO documents, i.e. Danish reservations towards a number of NATO and U.S. nuclear policies. Instead of calling for a general election, the Conservative-Liberal government decided to „coexist with“ the footnotes in order to remain in office. The result was domestic strife in Denmark as well as allied criticism. Since the 1980s, the „footnote policy“ has been debated by Danish historians. So far, however, most accounts have failed to examine to what extent the „footnote policy“ was related to the Social Democratic Party’s commitment to international party cooperation. Based on findings in Nordic labour archives as well as private archives from Denmark and Germany, it is argued that the security policy of the Social Democratic Party was largely inspired by discussions in the Socialist International, the UN appointed Independent Commission on Disarmament and Security Issues under the Chairmanship of Olof Palme, and the Social Democratic transnational discussion group Scandilux. It is however also argued that the „footnote policy“ cannot be fully understood if the domestic perspective is not included in the analysis.